2017
DOI: 10.1590/1980-5373-mr-2016-1035
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintering of a Hard Metal Powder Obtained from Hard Metal Scrap

Abstract: Spark plasma sintering is used to consolidate a WC-Co powder produced from milled discharged hard metal cutting inserts. The powder was mixed to 10%wt Co powder and spark plasma sintered (SPS) under 80Mpa pressure, at 1200ºC with heating rate of 160ºC/min. A reference alloy was prepared with a commercial WC powder and 10%wt. Co under the same conditions. The structures of both alloys were investigated by means of scanning electron microscopy and Vickers hardness. The results show structures with densities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Saleiro and Holanda [46] identi ed that a red clay body sintering at HRs of 1, 10 and 20°C/min culminated in similar properties, favoring energy savings. Santos et al [47] sintered hard metal alloys via pulsed plasma with HRs above 50°C/min and found that the structure densi cation rate has a HR dependence. In fact, it is well known that pulsed plasma sintering can densify structures in short time intervals and one of the characteristics of this technique is the high HR employed.…”
Section: Resultsmentioning
confidence: 99%
“…Saleiro and Holanda [46] identi ed that a red clay body sintering at HRs of 1, 10 and 20°C/min culminated in similar properties, favoring energy savings. Santos et al [47] sintered hard metal alloys via pulsed plasma with HRs above 50°C/min and found that the structure densi cation rate has a HR dependence. In fact, it is well known that pulsed plasma sintering can densify structures in short time intervals and one of the characteristics of this technique is the high HR employed.…”
Section: Resultsmentioning
confidence: 99%
“…It allows sintering at lower temperatures between 200°C and 500°C compared to traditional sintering methods. Evaporation, melting and sintering is completed between 5-and 20-minutes including temperature rise time [6,7].…”
Section: Introductionmentioning
confidence: 99%